Paullinia cupana (Kunth) stimulates behavior patterns and regulates oxidative stress markers in lobster cockroach Nauphoeta cinerea - Oliveira, Thalyta Julyanne Silva de; Viana, José Wellington Macêdo; Pereira, Pedro Silvino; Morais, Elayne Eally Silva de Oliveira; Silva, Jailson Renato de Lima; Oliveira , Carlos Vinícius Barros de; Costa, Adrielle Rodrigues; Menezes, Irwin Rose Alencar de; Duarte, Antonia Eliene; Kamdem, Jean Paul; Barros, Luiz Marivando (Brazilian Journal of Science, 2022)
Paullinia cupana (Kunth), popularly known as guarana, is a plant species from the Amazon Region of Brazil that stands out for being one of the most promising herbal medicines of the Brazilian flora since it has relevant biological properties. However, studies are still needed to use this species as a direct approach to evaluate aspects related to behavior and oxidative stress in invertebrate model animals. In this context, we aimed to evaluate the stimulant and the antioxidant effects of P. cupana in lobster cockroach Nauphoeta cinerea. For that, cockroaches were exposed to a diet separately supplemented by the decoction of P. cupana powder decoction at increasing concentrations of 1, 25, 50 and 100 mg/g for 42 days. Behavioral and biochemical assays were performed, respectively, to assess the locomotor/exploratory performance and oxidative stress marker levels of the cockroaches. They exhibited an outstanding increase in the locomotion performance and in the cell viability content, as well as in the protein and non-protein thiol levels. Moreover, there was a decrease in lipid peroxidation levels and in free Fe2+ ion contents. Together, our results demonstrate the stimulant and the antioxidant capacity of P. cupana by acting positively in behavioral patterns and by regulating oxidative stress markers in lobster cockroach N cinerea. These findings encourage further laboratory analyzes in order to better enlighten the specific mechanisms of action attributed to guarana.